Novel neurosteroid pregnanolone pyroglutamate suppresses neurotoxicity syndrome induced by tetramethylenedisulfotetramine but is ineffective in a rodent model of infantile spasms - Chern, Chian-Ru; Lauková, Marcela; Schonwald, Antonia; Kudová, Eva; Chodounská, Hana; Chern, Chian-Jiang; Shakarjian, Michael P; Velíšková, Jana; Velíšek, Libor (Pharmacological reports, 2023)
BACKGROUND: Neurosteroids are investigated as effective antidotes for the poisoning induced by tetramethylenedisulfotetramine (TMDT) as well as treatments for epileptic spasms during infancy. Both these conditions are quite resistant to pharmacotherapy; thus, a search for new treatments is warranted. METHODS: In this study, we determined the efficacy of two novel neurosteroids, pregnanolone glutamate (PAG) and pregnanolone pyroglutamate (PPG), and tested these drugs in doses of 1-10 mg/kg (ip) against the TMDT syndrome and in our rodent model of infantile spasms. RESULTS: Only PPG in doses 5 and 10 mg/kg suppressed the severity of the TMDT syndrome and TMDT-induced lethality, while the 1 mg/kg dose was without an effect. Interestingly, the 1 mg/kg dose of PPG in combination with 1 mg/kg of diazepam was also effective against TMDT poisoning. Neither PAG nor PPG were effective against experimental spasms in the N-methyl-D-aspartate (NMDA)-triggered model of infantile spasms. CONCLUSIONS: While evidence suggests that PAG can act through multiple actions which include allosteric inhibition of NMDA-induced and glycine receptor-evoked currents as well as augmentation of ɣ-aminobutyric acid subtype A (GABAA) receptor-induced currents, the agent appears to neither have the appropriate mechanistic signature for activity in the infantile spasm model, nor the adequate potency, relative to PPG, for ameliorating the TMDT syndrome. The full mechanisms of action of PPG, which may become a potent TMDT antidote either alone or in combination with diazepam are yet unknown and thus require further investigation.
Keywords: neurosteroidy; Antidote; Pregnanolone; Pyrrolidonecarboxylic Acid; Tetramethylenedisulfotetramine; Animals; hlodavci; spasmus; Neurosteroids; křeče u dětí; neurotoxické syndromy; Diazepam; Spasms, Infantile; Rodentia; Glutamic Acid; N-Methylaspartate; Neurotoxicity; N-methylaspartát; kyselina pyrrolidonkarboxylová; pregnanolon; zvířata; Neurotoxicity Syndromes; kyselina glutamová; diazepam; Severe seizures; Spasm